2015
DOI: 10.1155/2015/747085
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characterization of Drug Resistance amongMycobacterium tuberculosisIsolated from Patients in Northeast of Iran during 2012-2013

Abstract: Introduction. Tuberculosis is still one of the most important health problems in developing countries and increasing drug resistance is the main concern for its treatment. This study was designed to characterize the drug resistant Mycobacterium tuberculosis isolated from patients suffering from pulmonary tuberculosis in northeast of Iran. Method. In this cross-sectional study during 2012-2013, drug susceptibility testing was performed on Mycobacterium tuberculosis isolated in northeast of Iran using proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Shamaei et al found 10 (2.8%) MTB isolates re-sistant to RIF + INH (29). In 2015, Tavanaee Sani et al reported 51 of 1,251 patients with MDR from Shariati Hospital, Mashhad, Iran(30). In this study, the frequency of MTB was similar to other Iranian studies with 3.8% frequency.…”
supporting
confidence: 87%
“…Shamaei et al found 10 (2.8%) MTB isolates re-sistant to RIF + INH (29). In 2015, Tavanaee Sani et al reported 51 of 1,251 patients with MDR from Shariati Hospital, Mashhad, Iran(30). In this study, the frequency of MTB was similar to other Iranian studies with 3.8% frequency.…”
supporting
confidence: 87%
“…Our results are similar to those of Asgarzade et al (19) and Namaei et al (20), but are not in agreement with those of Bahrami et al (21) and Xin Shen et al (22). The findings of the survey by Tavanaee et al (23) suggest that only 3% of the patients are EMB resistant in the east of Iran. The prevalence in our work is significantly lower than that reported in Latvia, Thailand, Mozambique, and Uganda by WHO (3) and the study by Plinke et al (24) that obtained a resistant rate of 63.5%.…”
Section: Discussionsupporting
confidence: 59%
“…Most studies were conducted in Tehran ( n = 25; Bahrmand et al, 2000 ; Mohammadi et al, 2002 ; Seyed-Davood Mansoori et al, 2003 ; Masjedi et al, 2006 ; Mirsaeidi et al, 2007 ; Mohammadzadeh et al, 2007 ; Farnia et al, 2008a , b ; Shamaei et al, 2009 ; Dinmohammadi et al, 2010 ; Merza et al, 2011 ; Ostadzadeh et al, 2011 ; Sheikholslami et al, 2011 ; Taghavi et al, 2011 ; Tasbiti et al, 2011 ; Derakhshani Nezhad et al, 2012 ; Marjani et al, 2012 ; Mohammadi, 2012 ; Tahmasebi et al, 2012 ; Bahrami et al, 2013 ; Ali et al, 2014 ; Nasiri et al, 2014 ; Sheikh Ghomi et al, 2014 ; Varahram et al, 2014 ; Velayati et al, 2014 ) and Tabriz ( n = 8; Hassan Heidarnejad and Nagili, 2001 ; Moadab and Rafi, 2006 ; Varshochi et al, 2006 ; Asgharzadeh et al, 2007 , 2014 ; Rafi et al, 2009 ; Roshdi and Moadab, 2009 ; Zamanlou et al, 2009 ). Other studies were performed in Khorasan ( n = 3; Namaei et al, 2006 ; Velayati et al, 2014 ; Sani et al, 2015 ), Ardebil ( n = 1; Velayati et al, 2014 ), Isfahan ( n = 3; Moniri, 2001 ; Nasiri et al, 2014 ; Velayati et al, 2014 ), Mazandaran ( n = 3; Pourhajibagher et al, 2012 ; Babamahmoodi et al, 2014 ; Velayati et al, 2014 ), Gilan ( n = 1; Velayati et al, 2014 ), Hamadan ( n = 1; Velayati et al, 2014 ), Kerman( n = 1; Velayati et al, 2014 ), Kurdistan( n = 1; Velayati et al, 2014 ), Yazd ( n = 1; Velayati et al, 2014 ), Qazvin ( n = 1; Velayati et al, 2014 ), Kermanshah ( n = 4; Izadi et al, 2011 ; Nasiri et al, 2014 ; Velayati et a...…”
Section: Resultsmentioning
confidence: 99%